Trade-Related Aspects of Intellectual Property Rights (TRIPS) Waiver Proposal for Global Health Equity in COVID-19 Pandemic: The Challenges and Dynamics - Lintania, Nabiila Putri; Maulana, Zain (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
The TRIPS waiver is a proposal by India with South Africa submitted to the WTO. The Proposal contains certain exceptions to the applicable TRIPS Agreement. This Waiver Proposal was submitted because of the inequity conditions between rich and poor countries accessing health products in eradicating the COVID-19 pandemic. This study aims to analyze the success of the TRIPS Waiver in fighting for equity distribution of global health facilities in the context of the COVID-19 pandemic from the start of the pandemic to the end of 2022 by examining the challenges and dynamics of the proposal submission process at the WTO. This study uses a qualitative descriptive method by reviewing literature or secondary data. In analyzing the challenges and dynamics of the TRIPS Waiver Proposal process at the WTO, the authors use the norm life cycle concept and find results that the internalization of norms has not been fully formed because the domination of big countries of WTO members have not agreed on all aspects of the TRIPS Waiver proposal, or it can be said that the TRIPS Waiver Proposal has not been fully agreed upon as a new norm in overcoming global health inequity. Even though the supporting tipping point has exceeded 1/3, full support is needed for the success of the TRIPS Waiver Proposal, as voting in the WTO is based on consensus. The novelty of this research is the use of the norm life cycle concept in the implementation process.